Adoption of mGovernment service initiative in developing countries: A citizen-centric public service delivery perspective - Apollos Patricks Oghuma; Myeong-cheol Park; Jae Jeung Rho (International Telecommunications Society (ITS), 2012)
The phenomenal advancement of mobile technologies and the large penetration of mobile phones in developing countries have provided alternative solutions to re-engineer public service delivery mechanism. Governments are now challenged to deliver an expanding set of services to citizen given the general pervasiveness and ubiquity of mobile devices. This development has given a growing focus on modernizing public service delivery to improve the efficiency and effectiveness of services. The devices have become the world's most common means of interpersonal communication and constituting the new frontier that is beginning to transform governance; making government more accessible and more citizen-centric by extending the dividends of governance. This emerging trend in public service delivery has been named mGovernment. This new paradigm shift of governance is the latest innovation and practice in developed countries. mGovernment has emerged as an appropriate form of governments' initiatives using mobile devices within the purview of government administration to deliver public services to citizens and organizations in a transparent, accountable, efficient and effective manner on mobile devices. The Public Private Partnership (PPP) model has been advocated because of the budgetary constraints of governments. This paper examines some of the factors for its successful implementation and the policy directions for governments and other stakeholders. The paper draws on concepts from multiple theoretical perspectives using the theory of diffusion and grounded theory to understand the proposition of the new initiative. The paper explores mGovernment potentials for transforming governance by increasing their accessibility and citizen-centricity. This study contributes to the literature on mGovernment by synthesizing best practices solutions for public service delivery and suggests a new business model for its sustenance. The paper also suggests policy direction to governments and stakeholders.
Keywords: 330; mGovernment; Cititzen-Centric Public service delivery; Mobile Technology; Mobile Services; Public-Private-Partnership model